2010
DOI: 10.4085/1062-6050-45.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Helmet Fit and Cervical Spine Motion in Collegiate Men's Lacrosse Athletes Secured to a Spine Board

Abstract: Context: Proper management of cervical spine injuries in men's lacrosse players depends in part upon the ability of the helmet to immobilize the head.Objective: To determine if properly and improperly fitted lacrosse helmets provide adequate stabilization of the head in the spine-boarded athlete.Design: Crossover study. Setting: Sports medicine research laboratory.Patients or Other Participants: Eighteen healthy collegiate men's lacrosse players.Intervention(s): Participants were asked to move their heads thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Although these results were not different, the increase in movement may be clinically important. This finding remains controversial because researchers 26 more recently have found that cervical spine motion was limited the most when lacrosse athletes wore no helmet rather than when they wore properly fitted or improperly fitted helmets. The authors concluded that the head can move inside the lacrosse helmet, making cervical spine immobilization of the helmeted lacrosse athlete difficult.…”
Section: Recommendations and Clinical Relevancementioning
confidence: 99%
“…Although these results were not different, the increase in movement may be clinically important. This finding remains controversial because researchers 26 more recently have found that cervical spine motion was limited the most when lacrosse athletes wore no helmet rather than when they wore properly fitted or improperly fitted helmets. The authors concluded that the head can move inside the lacrosse helmet, making cervical spine immobilization of the helmeted lacrosse athlete difficult.…”
Section: Recommendations and Clinical Relevancementioning
confidence: 99%
“…If the helmet and shoulder pads were in place, the participant performing ventilations was not allowed to manipulate or remove the chinstrap because a properly fitted helmet provides stability to the head and neck with a suspected spine injury. 4,18 For trials involving the OPA or KA, members of the research team properly inserted the device. Participants received no feedback on performance after each data-collection trial.…”
Section: Data-collection Proceduresmentioning
confidence: 99%
“…[24][25][26] There is a debate on whether helmet removal or FMR would be the best approach to access the airway. 19,24,25,27 Lacrosse helmet FMR can occur within a reasonable amount of time, to access the airway, in new helmets; 24,26 however, a failure rate of 22% has been shown in lacrosse helmets used for at least one season. 25 In a study that examined space available for the spinal cord in lacrosse athletes, it was noted that no significant difference existed between helmeted and nonhelmeted athletes.…”
Section: Introductionmentioning
confidence: 99%
“…25 In a study that examined space available for the spinal cord in lacrosse athletes, it was noted that no significant difference existed between helmeted and nonhelmeted athletes. 19 Also, head motion is best restricted on a spine board when the lacrosse helmet is removed, 27 suggesting that helmet removal may be more appropriate. However, no studies have examined how much motion occurs in the cervical spine with helmet removal.…”
Section: Introductionmentioning
confidence: 99%